Prevalence of Congenital Heart Disease in Chinese Children With Different Birth Weights and Its Relationship to the Neonatal Birth Weight - Yan, Hui; Zhai, Bo; Feng, Ruiling; Wang, Penggao; Zhang, Yaodong; Wang, Yiran; Hou, Yuwei; Zhou, Yang (Frontiers in Pediatrics, 2022)
Objective: To examine the prevalence and the related risk factors of congenital heart disease (CHD) in children with different birth weights in China as well as the relationship between the subtypes of CHD and birth weight (BW). Methods: This study conducted a cross-sectional survey on the data collected in the Chinese Children's Congenital Heart Disease Database (CHDD). The study included all the children and their parents in the database from 2014 to 2020 as the study subjects. We reported the prevalence of CHD based on birth weight and gestational age and the generalized linear model was used to assess the association between the subtypes of CHD and BW by establishing three adjusting models and the data were stratified for further analysis by urban-rural and infants's gender. Results: A total of 42814 children were identified as having CHD among 5071799 live children, the overall prevalence of CHD was 8.44 per 1000 live births during 2014-2020. The prevalence of CHD was 18.87‰ in the group with BW < 1500g, 12.84‰ in the group with BW 1500g ~ 2500g, 8.24‰ in the group with BW 2500g ~ 4000g, and 4.80‰ in the group with BW ≥ 4000g. The prevalence of CHD was 16.62‰ in small for gestational age (SGA) group, 6.99‰ in appropriate for gestational age (AGA) group and 6.40‰ in larger for gestational age (LGA) group.The results of Model 3 adjusting for confounding variables showed that infants with ASD had a birth weight 461g lower (95%CI: -1085, -128), infants with VSD had a birth weight 426g lower (95%CI: -932,-120), infants with TOF had a birth weight 532g lower (95%CI: -987,-168), without classification, infants with CHD had a birth weight 973g lower (95%CI: -1502,-204). Conclusion: In very low birth weight (VLBW) and low birth weight (LBW) infants CHD are more prevalent than in the general live born population. Different types of heart defects can lead to LBW. Therefore, if the fetus is found to have a heart defect during prenatal examination, the mother should pay more attention to maintaining weight and ensuring that the fetus is within the normal weight range.